Oxygen atomic flux O-* enhancement by gas-pulsed electron cyclotron resonance plasma - Park, YJ; OKeeffe, P; Ozasa, K; Mutoh, H; Aoyagi, Y; Min, SK (AMER INST PHYSICS, 1997)
We have investigated an oxygen gas-pulsed plasma in conjunction with the enhancement of atomic oxygen radical O* flux and its application. The measured mean O* flux of 5.9x10(15) atoms/cm(2) s from the gas-pulsed plasma with a duty cycle of 50% (periodically opened for 0.3 s and closed for 0.3 s) at 32 seem is 1.6 times enhanced compared to that of a continuous wave plasma and is in good agreement with the increment obtained with the time averaged value of transient optical emission profiles of O* at 777.6 nm. The generation of a higher O* flux was interpreted by the mitigation of a recombinative reaction process through the interruption of gas flow injections in the gas pulsed plasma. As a preliminary application, an increase in critical temperature of superconducting YBa2Cu3O7-x thin films was achieved by the gas-pulsed plasma oxidation with a duty cycle of 50%. (C) 1997 American Institute of Physics.
Keywords: BEAM EPITAXY; RADICAL-BEAM; GENERATION; FILMS